Recent Progress on Pebax-Based Thin Film Nanocomposite Membranes for CO2 Capture: The State of the Art and Future Outlooks - Nematollahi, Mohammad Hadi; Carvalho, Pedro J.; Coutinho, João A. P.; Abedini, Reza (Energy & fuels, 2022)
Over the past three decades, membrane technology has gained increasing relevance owing to its green and energy-efficient process. Among the existing membranes, thin-film composite/nanocomposite (TFC/TFN) membranes are the subject of an increasing number of studies due to their high gas flux, high selectivity, cost reduction, and the possibility to independently control and optimize the materials of each layer. This review examines the advancement in TFC/TFN membranes for CO2 sequestration. The structure of the multilayer composite membranes and the characteristics of each layer are initially presented. Various top-down and bottom-up approaches for the preparation of composite membranes are discussed in detail. The factors influencing TFC membranes are highlighted. The focus of this research is on the separation properties of the Pebax polymer. The impacts of nanofillers on the separation performance of Pebax-based TFN membranes are meticulously inspected. Finally, the most important challenges and future outlooks to improve the membrane performance are presented.